2011
DOI: 10.1055/s-0030-1259915
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of the Marine-Derived Cyclic Depsipeptide Alternaramide

Abstract: The first synthesis of the marine fungus derived natural product alternaramide is described using solution phase coupling protocols and via a macrolactonization and macrolactamization route. The structure of alternaramide was confirmed and was supported by single crystal X-ray analysis which exhibited three similar molecules in the asymmetric unit, each with transannular hydrogen bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The total synthesis of the two possible isomers of 2 , i.e., cyclo-(- N Ac- l -Thr- d/l -Leu- l -Phe- l/d -Leu- O -), was addressed (Figure A). Main issues that were encountered were (i) to prevent the acetyl amide hydrolysis and (ii) to induce the correct cyclization, since macrolactamization is kinetically favored over lactonization . To circumvent a late-stage macrolactonization, a Steglich esterification of N Ac-Thr and l -Leu/ d -Leu was carried out as an initial step that resulted in two isomeric amino acyl esters, N -Boc -d/l- Leu- O - N Ac- l -Thr-COOH.…”
Section: Resultsmentioning
confidence: 99%
“…The total synthesis of the two possible isomers of 2 , i.e., cyclo-(- N Ac- l -Thr- d/l -Leu- l -Phe- l/d -Leu- O -), was addressed (Figure A). Main issues that were encountered were (i) to prevent the acetyl amide hydrolysis and (ii) to induce the correct cyclization, since macrolactamization is kinetically favored over lactonization . To circumvent a late-stage macrolactonization, a Steglich esterification of N Ac-Thr and l -Leu/ d -Leu was carried out as an initial step that resulted in two isomeric amino acyl esters, N -Boc -d/l- Leu- O - N Ac- l -Thr-COOH.…”
Section: Resultsmentioning
confidence: 99%
“…As previous syntheses of depsipeptides showed that lactamization was preferred over lactonization [1314], the synthesis of 1 was performed as follows: briefly, the linear peptide was synthesized using solid-phase peptide synthesis, followed by esterification and subsequent cleavage from the resin, deprotection and cyclization to yield 1 , assisted by microwave irradiation at every stage with the exception of the esterification (Scheme 1). …”
Section: Resultsmentioning
confidence: 99%